Centralization of Local Government Authority in Mining Licensing Following the Enactment of the Mineral and Coal Law: Sentralisasi Terhadap Kewenangan Pemerintah Daerah Dalam Perizinan Tambang Pasca Pemberlakuan Undang-Undang Mineral Dan Batubara - Novita Eka Utami (Lex Renaissance, 2023)
After the enactment of Law Number 3 of 2020 on Minerals and Coal, there was a ‘tug-of-war’ over the authority of local and regional governments, resulting in centralized policies that resulted in a perceived lack of involvement of regional governments and community participation, which gave rise to controversy regarding mining permits. This research examines two problem formulations: First, how will regional government authority change in mining licensing after the enactment of Law Number 3 of 2020 on Minerals and Coal? Second, what is the impact post the enactment of Law Number 3 of 2020 on Minerals and Coal on society? The research method used is normative law by applying literature study. The results of the research concluded that: the existence of several articles that are considered centralistic is the main problem for regional governments because they eliminate articles containing the authority of regional governments, resulting in disharmony between centralization in Mining and Coal policies with regional autonomy and decentralization and these policies weaken the welfare of regional communities but are profitable for mining entrepreneurs.Keywords: Regional authority, Mining, Centralization AbstrakPasca Pemberlakuan Undang-Undang Nomor 3 Tahun 2020 tentang Mineral dan Batubara, terjadinya tarik menarik kewenangan pemerintah puat dan daerah yang memunculkan kebijakan sentralistik sehingga dianggap kurangnya pelibatan pemerintah daerah dan partisipasi masyarkat yang kemudian memunculkan kontroversi mengenai perizinan pertambangan. Penelitian ini mengkaji dua rumusan masalah: Pertama, bagaimana perubahan kewenangan pemerintah daerah dalam perizinan tambang pasca berlakunya Undang-Undang Nomor 3 Tahun 2020 tentang Mineral dan Batubara. Kedua, bagaimana dampak pasca berlakunya Undang-Undang Nomor 3 Tahun 2020 tentang Mineral dan Batubara terhadap masyarakat. Metode penelitian yang digunakan yaitu yuridis-normatif dengan menerapkan studi kepustakaan. Hasil penelitian menyimpulkan: adanya beberapa pasal yang dipandang sentralistik menjadi persoalan utama terhadap pemerintah daerah sebab menghapuskan pasal-pasal berisi kewenangan pemerintah daerah akibatnya terjadinya ketidak-harmonisan sentralisasi dalam kebijakan Minerba dengan otonomi daerah serta desentralisasi dan kebijakan tersebut melemah pada kesejahteraan masyarakat yang didaerah tetapi menguntungkan bagi pengusaha tambang.Kata Kunci: Kewenangan daerah, Pertambangan, Sentralisasi